(untitled) (Jurnal EurekaMatika, 2024)
Poverty is when a person cannot adequately fulfill his daily needs. The data is taken from the official website of the Papua Province Central Statistics Agency (BPS). The panel data regression method was analyzed with the help of the EViews 12SV lite version for students and the IBM SPSS Statistics 24. This research aims to examine the most influential factors causing poverty in Papua and obtain the best regression model. Based on the Chow test, Hausman test, significance test, and classical assumption tests, the best model for panel data regression for modeling poverty in Papua is the fixed effect model (FEM). The results of the analysis show that 99.78% of the poor population has a life expectancy, human development index, gross regional domestic product, labor force participation rate, and open unemployment rate. Meanwhile, the remaining 0.22% is explained by other variables outside the model. Life expectancy and the human development index have a significant effect, while gross regional domestic product, labor force participation rate, and open unemployment rate are not significant on the poor population in Papua in 2017-2020. ABSTRAK Kemiskinan merupakan sebuah keadaan dimana seseorang tidak dapat memenuhi kebutuhan hidupnya secara layak. Data penelitian diambil dari laman resmi Badan Pusat Statistik (BPS) Provinsi Papua. Penelitian menggunakan metode regresi data panel yang dianalisis dengan bantuan EViews 12SV versi lite untuk mahasiswa dan IBM SPSS Statistics 24. Tujuan dari penelitian ini yaitu menganalisis faktor penyebab kemiskinan yang paling berpengaruh di Papua dan mendapatkan model regresi terbaik. Berdasarkan uji Chow, uji Hausman, uji signifikansi dan uji asumsi klasik yang sudah dilakukan, model terbaik regresi data panel untuk pemodelan kemiskinan di Papua adalah model fixed effect model (FEM). Hasil analisis menunjukkan bahwa penduduk miskin dapat dijelaskan sebesar 99,78% dari angka harapan hidup, indeks pembangunan manusia, produk domestik regional bruto, tingkat partisipasi angkatan kerja dan tingkat pengangguran terbuka. Sedangkan sisanya 0,22% dijelaskan oleh peubah lain di luar model. Angka harapan hidup dan indeks pembangunan manusia berpengaruh signifikan, sedangkan produk domestik regional bruto, tingkat partisipasi angkatan kerja dan tingkat pengangguran terbuka tidak signifikan terhadap penduduk miskin di Papua tahun 2017-2020.